Environmentally friendly material and technological solutions of road pavements - Radziszewski, Piotr; Kowalski, Karol; Sarnowski, Michał; Pokorski, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
In recent years road construction is a subject of dynamic changes. The main challenge for designers and technologists is to develop durable and environmental friendly road technologies that can be successfully applied on natural valuable areas. The paper presents selected modern material and technological solutions used for road pavements on areas under special protection (eg Natura 2000). An example of modern environmentally friendly solutions in road construction are: asphalt pavements with the addition of rubber from used car tires, asphalt mixtures with reduced emissions of volatile substances, “quiet” pavements, pavements from recycled materials and from local materials, “biologically active” pavements (permeable mineral layers). Modern and ecological pavements are the important part of science activity of Warsaw University of Technology. New ongoing project is designed to identify the main directions of technological development of road construction in the next 30 years, with a particular emphasis on the sustainable development and environmental protection. As a part of the two ongoing projects, test sections of pavement have been completed. One of test sections with the addition of crumb rubber and the second one as a “quiet” pavement. For the next years, the sections will be monitored.The proper selection of materials and technologies on natural valuable areas does not deteriorate the durability of road pavement, comfort and safety on the roads and at the same time it can improve environmental safety without interfering with the functioning of valuable ecosystems.